Research in quantity surveying - Tan, Chin Keng (s.n, 2013)
This research project was conducted in conjunction with the IIUM;s Knowledge Virtue Camp (KVC) in 2011. The objective of the project was to publish an edited book entitled research in Quantity Surveying. The research grant was to help the funding of the publication of the book. The process of the research included reviewing, editing and formatting chapters of the book